Species Specificity of Aldehyde and Fatty Acid Profiles of Four Family Group Representatives within the Insect Infraorder Pentatomomorpha (Hemiptera: Heteroptera) - Tomčala, Aleš; Jirošová, Anna; Žáček, Petr; Kaušková, Markéta; Hovorka, Oldřich; Koutek, Bohumír (Chemistry & biodiversity, 2017)
Reactive α,β-unsaturated aldehydes, including 4-oxoalk-2-enals, are known to be present in volatile secretions of numerous heteropteran insect species. Because the aldehydes are likely to originate from metabolism of fatty acids (FAs), the present study aimed to examine and compare the aldehyde and FA profiles of four model heteropteran species. The model species consisted of adult family group representatives within the infraorder Pentatomomorpha (Hemiptera: Heteroptera): seed bug (Lygaeus equestris (Lygaeoidea)), dock leaf bug (Coreus marginatus (Coreoidea)), red firebug (Pyrrhocoris apterus (Pyrrhocoroidea)), and European stink bug (Graphosoma lineatum (Pentatomoidea)). Solid-phase microextraction combined with two-dimensional gas-chromatography/time-of-flight mass spectrometry was used to establish the profiles of volatile secretions in stressed living insects. The FA profiles of acylglyceride and phospholipid fractions deposited in fat body and/or hemolymph were obtained by liquid chromatography/mass spectrometry and gas chromatography with flame ionization detection techniques. Our results based on multivariate statistical analyses of the data imply that volatile secretion blends as well as fat body and/or hemolymph lipid profiles are species specific but the differences in volatile blends between different species do not mirror the changes in corresponding fat body and/or hemolymph lipid profiles of stressed and non-stressed individuals.
Keywords: mikroextrakce na pevné fázi; fyziologický stres; druhová specificita; Unsaturated aldehydes; Fat body; Fat Body; tukové těleso; zvířata; Defensive compounds; Stress, Physiological; mastné kyseliny; plynová chromatografie s hmotnostně spektrometrickou detekcí; Hemolymph; Triacylglycerol; Species Specificity; Heteroptera; Pentatomomorpha; aldehydy; Animals; Gas Chromatography-Mass Spectrometry; Aldehydes; hemolymfa; Solid Phase Microextraction; Fatty Acids